Resistance Status of the Colorado Potato Beetle, Leptinotarsa decemlineata, to Endosulfan in East Azarbaijan and Ardabil Provinces of Iran - Mohammadi Sharif, M. (University of Wisconsin Library, 2007)
Three Colorado potato beetle, Leptinotarsa decemlineata, populations, from Ardabil, Bostanabaad and Ajabshir, were collected from potato fields in East Azarbaijan and Ardabil provinces in Iran and assayed for resistance to endosulfan. Possible resistance mechanisms were investigated using synergism studies and biochemical assays. Laboratory tests showed that the Bostanabaad strain was 220 and 109 times resistant compared with the susceptible strain in 2003 and 2004, respectively. The resistance ratios for the Ajabshir and Ardabil strains were 19 and 18, respectively. Since considerably more resistance was observed in the Bostanabaad strain compared with the other two, further investigation of the origin of resistance was done on this strain. Two insecticide synergists, piperonyl butoxide and S,S,S-tributylphosphorotrithioate, reduced resistance 2.3 and 3.5 times, respectively. These small degrees of synergism suggest that metabolism is not the source of the considerable difference in susceptibility between the two strains. This was supported by the results obtained from the biochemical assays that showed that glutathione S-transferase activity in the Bostanabaad strain did not significantly differ from the susceptible strain. These results suggest that target site insensitivity may be involved.